Sir John M. Templeton has passed away (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2008)
John Marks Templeton, the pioneer global investor who founded the Templeton Mutual Funds and for the past three decades devoted his fortune to his Foundation’s work on the “Big Questions” of science, religion, and human purpose, passed away on July 8, 2008. This text is a reprint of the annoucment from .